Accounting Manual for Small Cities of the State of Washington. - Miller, Herbert E.; Ludberg, C. C. (The Accounting Review, 1946)
Abstract Reviews the book "Accounting Manual for Small Cities of the State of Washington," by Arthur N. Lorig.